2007
DOI: 10.1177/0093854806297555
|View full text |Cite
|
Sign up to set email alerts
|

Five Factor Model Personality Traits, Jury Selection, and Case Outcomes in Criminal and Civil Cases

Abstract: Actual venire members ( N = 764) completed the Big Five Inventory before going through the jury selection process for 1 of 11 criminal or 17 civil trials. Jury selection decisions by attorneys were not associated with juror personality traits but were associated with juror race and sex, especially in criminal cases. In the 17 juries that deliberated to a verdict ( n = 285), high levels of juror extraversion were associated with not guilty verdicts or verdicts for the defendant, especially in criminal cases. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 33 publications
(46 reference statements)
2
30
0
Order By: Relevance
“…Only scarce evidence is yet available on the relationship between the broad bandwidth personality traits and punitive attitudes. The few studies that did investigate this issue mainly focused on capital punishment (Robbers, 2006;Lester & Maggioncalda-Aretz, 1997;McKelvie & Daoussis, 1982;McKelvie, 1983; but for an exception, see Clark et al, 2007). No previous studies have combine broadband personality and social attitudes in a multi-layer model explaining punitive attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only scarce evidence is yet available on the relationship between the broad bandwidth personality traits and punitive attitudes. The few studies that did investigate this issue mainly focused on capital punishment (Robbers, 2006;Lester & Maggioncalda-Aretz, 1997;McKelvie & Daoussis, 1982;McKelvie, 1983; but for an exception, see Clark et al, 2007). No previous studies have combine broadband personality and social attitudes in a multi-layer model explaining punitive attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Since, previous studies found mixed results (Robbers, 2006;Clark et al, 2007;McKelvie & Daoussis, 1982;McKelvie, 1983;Lester & Maggioncalda-Aretz, 1997), we aim to explore all direct and indirect 9 Running Head: PUNITIVE ATITTUDES relationships between broad bandwidth personality factors, social attitudes and punitive attitudes. However, we expect Neuroticism, Extraversion and Openness to experience to be related with Harsh Punishment.…”
Section: Toward An Integrative Model Of Dispositional Variables and Pmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies found that (i) male jurors are more influential on their peers than females (Mills and Bohannon, 1980;Marcus, et. al, 2000), (ii) higher socioeconomic status jurors are more influential (York and Cornwell, 2006), and (iii) more extraverted jurors are more influential (Clark et al, 2007;Marcus et al, 2000). These studies often use small case samples and are based on the 'selected' seated jury.…”
Section: ! !mentioning
confidence: 99%
“…Furthermore, research has shown that the Big 5 traits are related to judgment and decision-making across a variety of contexts, including jury decisions (Clark, Boccaccini, Caillouet, and Chaplin, 2007), entrepreneurial business ventures (Wooten, Timmerman, and Folger, 1998), and decisions to engage in risky health-related behaviors (Trobst, Wiggins, Costa, Herbst, McCrae, and Masters, 2000). The Big 5 are purported to affect decision making by influencing confidence/overconfidence in decisions, sensitivity to information from the environment (McElroy and Down, 2007), and heuristic biases (Trobst et al, 2000).…”
Section: Survey Instrumentmentioning
confidence: 99%